2010
DOI: 10.1002/polb.22013
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evolution and orientation development of stretched iPP films: Influence of draw ratio

Abstract: Varying the processing conditions of semicrystalline polymers can produce different morphologies of crystallization, which leads to different properties. There have been extensive studies of flow-induced crystallization on isotactic polypropylene (iPP) using predominantly shear flow. A stretching method, deduced from extrusion, was introduced to study the morphological evolution of elongation-induced shish-kebab crystallization. Different morphologies of the resultant samples with different draw ratios (DRs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 36 publications
0
41
2
Order By: Relevance
“…23,24 Chatterjee et al reported excellent barrier and optical properties for blown high-density polyethylene (HDPE) lms with optimized draw ratios to achieve special lamellar organization as well as orientation of the amorphous phase. Melt stretching is an effective way to induce chain extension and enhance molecular orientation, thus improving the mechanical properties of polyolens.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Chatterjee et al reported excellent barrier and optical properties for blown high-density polyethylene (HDPE) lms with optimized draw ratios to achieve special lamellar organization as well as orientation of the amorphous phase. Melt stretching is an effective way to induce chain extension and enhance molecular orientation, thus improving the mechanical properties of polyolens.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] The higher intensity of elongation ow eld results in the higher degree of orientation of lamellar crystalline along the draw direction. [16][17][18][19] The higher intensity of elongation ow eld results in the higher degree of orientation of lamellar crystalline along the draw direction.…”
Section: Resultsmentioning
confidence: 99%
“…The elastic polymer usually has been suggested to obtain the large elastic region for the conductive composite capable of substantial stretching and bending. 18,19 The morphology evolution of matrix have a profoundly inuence on the composite mechanical property, which correlates with the piezoresistive of composites. 15 By playing with lamellar crystalline structure through special processing method, the polyolen may be promising candidate for use in the highly stretchable electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained XRD images were further analyzed using a Bruker AXS general area detector diffraction system (GADDS). Following the same method in Zhou et al's paper, 28 the orientation of iPP crystals was quantified using the Hermans orientation function,…”
Section: Experimental Designmentioning
confidence: 99%